Recent advances in neuropeptide signaling in Drosophila, from genes to physiology and behavior - Nässel, Dick R.; Zandawala, Meet (Progress in neurobiology, 2019)
This review focuses on neuropeptides and peptide hormones, the largest and most diverse class of neuroactive substances, known in Drosophila and other animals to play roles in almost all aspects of daily life, as w;1;ell as in developmental processes. We provide an update on novel neuropeptides and receptors identified in the last decade, and highlight progress in analysis of neuropeptide signaling in Drosophila. Especially exciting is the huge amount of work published on novel functions of neuropeptides and peptide hormones in Drosophila, largely due to the rapid developments of powerful genetic methods, imaging techniques and innovative assays. We critically discuss the roles of peptides in olfaction, taste, foraging, feeding, clock function/sleep, aggression, mating/reproduction, learning and other behaviors, as well as in regulation of development, growth, metabolic and water homeostasis, stress responses, fecundity, and lifespan. We furthermore provide novel information on neuropeptide distribution and organization of peptidergic systems, as well as the phylogenetic relations between Drosophila neuropeptides and those of other phyla, including mammals. As will be shown, neuropeptide signaling is phylogenetically ancient, and not only are the structures of the peptides, precursors and receptors conserved over evolution, but also many functions of neuropeptide signaling in physiology and behavior.